Pentingnya Administrasi Pendidikan dalam Proses Belajar Mengajar - Sari, Putri Zulva; Sima, Shinta; Putri, Tazira Dwi (AL-HANIF: Jurnal Pendidikan Anak dan Parenting, 2022)
Learning is very meaningful for all humans, because humans are created to seek knowledge in learning that is expected from birth to death. Learning has its own level, starting from the most basic education (PAUD), then Elementary School / Madrasah Ibtidaiyah, Junior High School / Madrasah Tsanawiyah, and High School / Madrasah Aliyah. Each lesson has its own administration to meet learning needs. Educational administration has developed issues such as: 1) Constitution and learning policies, 2) Curriculum learning, 3) Teachers and learning, 4) national tests, 5) Access to learning, 6) Quality of learning, 7) Learning technology. There are many more problems or issues in the administration of education. The aim is to identify the benefits of educational administration, the functions of educational administration, and the objectives of educational administration. This research has the result that the main function of education administration is so that learning can be a better reference for educational administration problems in schools. so the importance of education administration to manage schools and learning well